(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article analyzes the peculiarities and problems of pantomime directing. Experiences of pantomime reformers and directors in pantomime performances will be studied. The differences between professional and amateur directing are highlighted. There is talk of pantomime directing education and its importance.